An investigation Into stylistic features Of special occasion speeches In english and vietnamese - Nguyễn Thị Hương Trinh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis examined stylistic features of prominent stylistic devices in special occasion speeches by American and Vietnamese presidents. The data of the study were collected from some famous books and websites on the internet. The data were described and analyzed on stylistic aspects under qualitative and quantitative approaches to yield more precise points on stylistic devices in special occasion speeches by the presidents. On a close analysis, the thesis tried to find out some commonly used stylistic devices in political language in special occasion speeches, namely repetition, stylistic inversion, enumeration and parallel construction and to find out the similarities and differences in stylistic features of these devices. With a hope of contributing to better teaching and learning English as a foreign language, especially to better the awareness of learners in understanding and writing a persuasive and interesting speech, some suggested ideas were also included.